2011
DOI: 10.1007/978-1-4419-9514-8
|View full text |Cite
|
Sign up to set email alerts
|

Random Matrices, Random Processes and Integrable Systems

Abstract: This is an expository account of the edge eigenvalue distributions in random matrix theory and their application in multivariate statistics. The emphasis is on the Painlevé representations of these distribution functions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This is interesting, since the information about the spectrum of the theory should be in principle extractable from such a representation. A paper where kernels with a similar structure are studied is [89] and a detailed review can be found in the lectures by van Moerbecke in [90]. The context of those studies is "Probability on Partitions and the Plancherel measure".…”
Section: Jhep07(2020)157mentioning
confidence: 99%
“…This is interesting, since the information about the spectrum of the theory should be in principle extractable from such a representation. A paper where kernels with a similar structure are studied is [89] and a detailed review can be found in the lectures by van Moerbecke in [90]. The context of those studies is "Probability on Partitions and the Plancherel measure".…”
Section: Jhep07(2020)157mentioning
confidence: 99%
“…Here the sums run from µ i = 1 rather than µ = 0, because the only contribution of µ i = 0 terms to connected correlation functions is the term N x 1 of W 1 , that we wrote separately. Let us draw an example of such a discrete surface, with genus g = 2 and n = 3 holes with (µ 1 , µ 2 , µ 3 ) = (5,6,4). Marked edges are denoted by arrows which follow the orientation of the surface, so that the hole is always on the left of the arrow:…”
Section: Expectation Valuesmentioning
confidence: 99%